2005
DOI: 10.1038/sj.bjc.6602309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the histone deacetylase inhibitor valproic acid on Notch signalling in human neuroblastoma cells

Abstract: Neuroblastoma (NB), a sympathetically derived childhood tumour, shows characteristics of neuronal precursor cells, suggesting a halted differentiation process. We have previously shown that the Notch signalling cascade, a key player during normal neurogenesis, also might be involved in NB differentiation. Valproic acid (VPA), a well-tolerated antiepileptic drug, has been shown to induce differentiation and cell death of NB cells, possibly associated with its recently described HDAC inhibiting activity. Stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 42 publications
8
104
0
Order By: Relevance
“…It can be speculated that the VPA effect on GSC viability could partially be a consequence of the interference on Notch/Hedgehog cascades, with important implications in glioma therapy. In support to our findings, several reports underlined the mis-regulation of Notch signaling cascade mediated by VPA as a novel strategy for cancer therapy (46,51,52).…”
Section: Discussionsupporting
confidence: 77%
“…It can be speculated that the VPA effect on GSC viability could partially be a consequence of the interference on Notch/Hedgehog cascades, with important implications in glioma therapy. In support to our findings, several reports underlined the mis-regulation of Notch signaling cascade mediated by VPA as a novel strategy for cancer therapy (46,51,52).…”
Section: Discussionsupporting
confidence: 77%
“…However, how acetylation and deacetylation control Notch pathway remains to be clarified. It has been observed that HDACi promote differentiation and cell death of neuroblastoma cells, likely due to suppression of Notch signaling (Stockhausen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…VPA has been shown to inhibit growth in several tumor cell lines (13,19,20,24). To date, the effect of VPA treatment on SCLC cell growth has not been characterized.…”
Section: Vpa Inhibits Proliferation Of Sclc Cellsmentioning
confidence: 99%
“…We have previously shown that Notch1 signaling is minimal or absent at baseline in several NET cell lines, and that expression of exogenous Notch1 via an inducible construct inhibits NET cell growth (6,14). Additionally, VPA has been reported to activate Notch1 signaling in neuroblastoma, carcinoid, and medullary thyroid cancer cells (13,19,20). We hypothesized, then, that VPA may also activate Notch1 signaling in SCLC cells with subsequent anti-tumor effects.…”
Section: Introductionmentioning
confidence: 99%